THE CORRELATION BETWEEN STUDENTS’ SELF-ESTEEM AND SPEAKING ACHIEVEMENT OF UNDERGRADUATE EFL STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF ISLAMIC STATE UNIVERSITY OF RADEN FATAH PALEMBANG - joni gunawan (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The main purpose of the present study was to empirically investigate the possible correlation and the influence between students’ self-esteem and speaking achievement. Students in the fifth semester were selected from among undergraduate EFL students of English Education study program at UIN Raden Fatah Palembang as the sample. Speaking test was done to measure students’ speaking achievement. By using oral Proficiency categories from Brown (2004) students’ speaking achievement was scored the five subskills of vocabulary, structure, pronunciation, fluency and comprehensibility. An adult version of Coopersmith self-esteem inventory (CSEI) which modified by Ryden (1978) for measuring self-esteem containing 58 items were also administered to the participants. Pearson product moment and regression analysis were used to find out the correlation and the influence between variables. The result showed that there was a significant correlation between students’ self-esteem and speaking achievement with r = .635. Besides, there was also a significant influence of self-esteem on speaking achievement with 40,4%. This study could have implications for English language teachers, course designers, learners, and text book writers. Index Terms - self-esteem, speaking achievement, testing speaking, UIN learners of English